The effect of adenoidectomy on occlusal development and nasal cavity volume in children with recurrent middle ear infection. Issue 12 (December 2015) - Niemi, P.; Numminen, J.; Rautiainen, M.; Helminen, M.; Vinkka-Puhakka, H.; Peltomäki, T.
Abstract: Objectives: The aim of the study was to examine the effect of adenoidectomy on occlusal/dentoalveolar development and nasal cavity volume in children who underwent tympanostomy tube insertion with or without adenoidectomy due to recurrent episodes of middle ear infection. Methods: This prospective controlled study consisted of two randomly allocated treatment groups of children, younger than 2 years, who had underwent more than 3–5 events of middle ear infection during the last 6 months or 4–6 events during the last year. At the mean age of 17 months tympanostomy tube placement without adenoidectomy (Group I, n = 63) tympanostomy tube placement with adenoidectomy (Group II, n = 74) was performed. At the age of 5 years 41 children of the original Group I (14 females, 27 males, mean age 5.2 yrs, SD 0.17) and 59 children of the original Group II (17 females, 42 males, mean age 5.2 yrs, SD 0.18) participated in the re-examination, which included clinical orthodontic examination defining morphological and functional craniofacial status and occlusal bite index to measure upper dental arch dimensions. Acoustic rhinometry and anterior rhinomanometry was made by otorhinolaryngologist at the same day. Results: No statistically significant differences were found between the groups in the frequencies of morphological or functional characteristics or upper dental arch measurements or in the minimal cross-sectional areas or inspiratory nasal airway resistance measurements. Conclusion: Combining adenoidectomy with tympanostomy tube insertion in the treatment of recurrent middle ear infection at an early age (under the age of 2 years) does not seem to make any difference in occlusal development in primary dentition at the age of 5 years as compared to tympanostomy tube insertion only. Since adenoid size was not evaluated, the findings do not allow interpretation that hypertrophic adenoids should not be removed in children with continuous mouth breathing or sleep disordered breathing.